Optimalisasi Kualitas Hasil Belajar dan Aktivitas Belajar Matematika Melalui Implementasi Model Cooperatif Learning Bersetting Teams Games Tournaments (TGT) Berbasis LKS - Ni Made Serma Wati; Ni Nyoman Serma Adi (Emasains : Jurnal Edukasi Matematika dan Sains, 2021)
This study aims to determine the optimization of the cooperative learning model with LKS-based Teams Games Tournaments to increase learning activities and mathematics learning outcomes of class X BBU 1 students of SMA Surya Wisata Kediri. This type of research is a Classroom Action Research (PTK) using the Research Design Model of Kemmis and Taggart. Subjects in this study were 40 students of class X BBU 1 SMA Surya Wisata Kediri. The data collection technique was carried out by means of observation and learning outcomes tests which were carried out in two cycles. Research instruments in the form of observation sheets and learning outcomes tests. Data analysis was performed by qualitative descriptive analysis. The results showed that the Optimization of Mathematics Learning through the Implementation of Cooperative Learning Model with Teams Games Tournaments (TGT) based on LKS can increase the activity and learning outcomes of students of class X BBU 1 SMA Surya Wisata Kediri. This is evident from the average value of student learning activities on the initial reflection 23.72 is in the less active category. Then there was an increase in cycle 1 with an average of 27.28 learning activities in the active category, and in the second cycle the average learning activity was 34.25 in the active category. While student learning outcomes also increased where individual completeness increased from 12 people (30%) in the initial reflection to 23 people (57.5%) in the first cycle and from 23 people (57.5%) in the first cycle to 35 people ( 87.5%) in cycle II. So based on the results of the research it can be concluded that the optimization of mathematics learning through the implementation of the cooperative learning model with the setting of Teams Games Tournaments (TGT) based on LKS can increase the activity and learning outcomes of students of class X BBU 1 SMA Surya Wisata Kediri.